Assessment of Clinical and Laboratory Predictors for Chronic Childhood Immune Thrombocytopenia - Sedef Alpdoğan; Hüseyin Gülen (Galenos Yayinevi, 2023)
Aim: To determine the risk factors associated with chronic childhood immune thrombocytopenia (ITP). Materials and Methods: We retrospectively analyzed the medical records of 123 children with ITP who were admitted to our Department of Pediatric Hematology between May, 2006 and May, 2019. We evaluated their demographic, clinical, and laboratory characteristics, and assessed the risk factors associated with chronic ITP in childhood. Results: Of the 123 children with ITP, 60.2% were male, with an average age of 6.4±4.0 years. At follow-up, 93 (75.6%) of the patients were diagnosed as acute ITP, whereas 30 (24.4%) progressed to chronic ITP with a platelet count of lower than 100×109/L at the end of the 12-month follow-up period. Older age at admission [Odds ratio (OR): 1.4, 95% confidence interval (CI): 1.2-1.6, p<0.001], female gender (OR: 4.1, 95% CI: 1.5-10.3, p=0.003), and insidious onset of the symptoms (OR: 5.0, 95% CI: 1.1-22.6, p=0.03) were determined to be risk factors for chronic ITPConclusion:Our study indicates that older age, female gender and insidious onset of the disease at admission may predict chronic ITP in childhood.